Creative Food Product of Healthy Puffed Riceberry Snack Bar Developed by Private-Community-University Collaborations - Panyoyai, Naksit; Wattanakul, Watcharapong; Suwannalers, Piluntasoot; Bunsongthae, Akharasit; khumcharoen, Sakunrat; Kaima, Prakaydao; Prompratan, TongMed; Kaewyodkong , Wannipa (Department of Technology of Agricultural product (THP) Jambi University, 2024)
“Riceberry” a variety cultivated for its high anthocyanin content, offers bio-functional benefits. The development of Riceberry products not only enriches the nutritional profile but also adds a creative dimension to the One Tambon One Product (OTOP) initiative of Thailand. The collaborative effort of Hin Kling, a community enterprise in Nakhon Sawan, Chiang Mai Rajabhat University (CMRU), and the support from the Petroleum Authority of Thailand (PTT) Public Company Limited, has been instrumental in this venture. Adopting the Four Ps model (process, product, packaging, and product marketing), the collaboration focused on refining production processes, ensuring product quality, providing informative packaging, and devising effective marketing strategies. The study revealed that saturated fat content was reduced by two-fold through the innovative approach of blending palm oil with soybean oil for frying puffed rice. The resulting puffed rice was then combined with various ingredients and shaped into bars, offering a product with a commendable shelf life of up to three months. Moreover, a commitment to health was demonstrated by reducing the added palm sugar, leading to lower sugar content, reduced calories, and improved texture in the healthier product. Rigorous quality checks, including water activity value, anthocyanin content, and total and pathogenic bacteria count, ensured that the product met the standards set for cereal bars. To enhance consumer awareness, the product's nutritional value was highlighted through a detailed nutritional facts section on the food label. Additionally, a captivating community story was crafted to introduce the health-focused product to the wider health food market. The three-party collaboration behind the Riceberry initiative has successfully delivered a bio-functional, nutritious, and creatively presented product tailored for health-conscious consumers.